Strategi Guru dalam Mengembangkan Efektivitas Pembelajaran Matematika di SDN No. 139/III Lempur Mudik - Nia Daniati; Nazurty Nazurty; Eddy Haryanto (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research was carried out based on the implementation of the mathematics learning process carried out by the teacher. The problems encountered are that there are still many obstacles experienced by teachers in learning mathematics. This is evident from the not optimal mathematics learning process carried out by the teacher. This research is a qualitative research that aims to determine the strategies used and applied by teachers in the smooth implementation of mathematics learning at SDN No. 139/III Lempur Mudik Kerinci Regency. The research subject is the teacher of SDN No. 139/III Lempur Mudik is a fourth grade teacher, where the data taken are in the form of observation data, interviews, and documentation. This research is expected to produce the right strategy for teachers in the implementation of mathematics learning while still paying attention to the conditions and readiness of teachers and students